2003
DOI: 10.1016/s0014-5793(03)00435-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tiam1–Rac signalling

Abstract: The GTPases of the Rho family are molecular switches that play an important role in a wide range of cellular processes and are increasingly implicated in tumourigenesis. Unlike what was found for the Ras oncogenes in tumours, hardly any activating mutations have been found in the genes encoding Rho proteins. In the past, we have identi¢ed Tiam1 (T-lymphoma invasion and metastasis) as a speci¢c activator for the Rholike GTPase Rac. In vivo, Tiam1 de¢ciency protects against Ras-induced skin carcinogenesis, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 42 publications
6
172
1
2
Order By: Relevance
“…4E), suggesting that CK1␦ may phosphorylate Ser/Thr residues in these two fragments and trigger ␤-TrCP recognition. Tiam1-C1199, a well characterized, constitutively active form lacking an N terminus (22,44), was also recognized by ␤-TrCP (Fig. 4F).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4E), suggesting that CK1␦ may phosphorylate Ser/Thr residues in these two fragments and trigger ␤-TrCP recognition. Tiam1-C1199, a well characterized, constitutively active form lacking an N terminus (22,44), was also recognized by ␤-TrCP (Fig. 4F).…”
Section: Resultsmentioning
confidence: 96%
“…T cell lymphoma invasion and metastasis 1 (Tiam1) serves as a specific GEF for Rho GTPase Rac1 (16). Although it has been well established that Tiam1 plays important roles in tumor progression and metastasis (17)(18)(19)(20), the specific mechanisms regulating its activity and protein stability are far from clear (21,22). It has been reported that Src-induced adherens junction disassembly and cell migration involve phosphorylation and degradation of Tiam1, likely through calpain proteases (20).…”
mentioning
confidence: 99%
“…In these circumstances, Tiam-1 was also located at lateral membranes. Tiam-1 has several distinct domains and binding partners, which are well described by Mertens et al (2003). Membrane translocation of Tiam-1 is crucial for its capacity to induce Rac-mediated membrane ruffles and activation of c Jun N-terminal kinase.…”
Section: Palovuori Et Almentioning
confidence: 99%
“…Membrane translocation of Tiam-1 is crucial for its capacity to induce Rac-mediated membrane ruffles and activation of c Jun N-terminal kinase. The first integral membrane protein reported to directly interact with Tiam-1 is the hyaluronic acid receptor isoform CD44 v3 , and the same domain of Tiam-1 also interacts with ankyrin (Mertens et al, 2003). These interactions might be involved in the complex processes of apoptosis and differentiation of MDCK cells where Tiam-1 and PDGF seem to play an active role.…”
Section: Palovuori Et Almentioning
confidence: 99%
“…Huam Tiam 1 gene maps to the syntenic region (q22) on human chromosome 21 (21q22) and encodes a 170 kDa transmembrane glycoprotein with intrinsic Rho GTPases activity, which contains a DH (Dbl homologous) domain adjacent to PH (Pleckstrin homologous) domain, a typical structure of guanine nucleotide exchange factors (GEFs) (Habets et al, 1995). As a specific GEF for Rac 1 (ras-related C3 botulinum toxin substrate 1), a member of Rho oncogene family, Tiam l can catalyze the transition of Rac l from inactive GDP-bound state to active GTPbound state, and then the latter one activates downstream signaling pathways related to many important cellular events, such as cytoskeletal reorganization, cell adhesion and migration (Mertens et al, 2003). Accordingly, Tiam 1 has been shown to increase invasion in T-lymphoma cells, as well as to stimulate cellular migration in fibroblasts, and to promote motility in some neurocytes.…”
Section: Introductionmentioning
confidence: 99%